ANALISIS RANTAI NILAI KOMODITAS IKAN AIR TAWAR UNGGULAN DI KOTA TANGERANG - Mentari Argarini; Akhmad Riyadi Wastra; Rizki Adi Puspita Sari (Departement of Agribusiness Faculty of Science and Technology, 2017)
This research is used to view the condition of the commodities value chain of freshwater fish featured in order to achieve food stability in Tangerang. The purpose of this study were 1) to analyze the type of commodity freshwater fish seed, 2) identify commodity supply chain of freshwater fish seed, 3) analyze, identify, and map the commodity value chain of freshwater fish seed and 4) analyze the value added resulting from all actors involved in the chain of freshwater fish commodity featured in Tangerang. This research was conducted in the city of Tangerang. The analysis is the MPE analysis, supply chain, value chain and value added Hayami method. Commodities of freshwater fish are catfish featured with 155,130,122.9. Catfish supply chain involves four actors, including farmers, traders, traditional market traders and traders of processed fish. Conditions of supply chain and value chain has not been effective and efficient, especially on farmers due to limited production and margin gap. Obtained the largest margin of processed fish merchant IDR 4.4892,05/kg, while the smallest margin in farmers IDR 152,22/kg. Calculation of value added at IDR 5.532,96/kg farmers, traders IDR 2.368,23/kg, traditional market traders IDR 2061.44/kg and processed fish merchant IDR 3.578,16/fish, or IDR 2.5047,12/kg. The biggest value added obtained traders processed fish, whereas the smallest value added obtained by farmers. Therefore, as a regulator and facilitator, the government has to be increase the value added and optimize fisheries production in Tangerang.